2021
DOI: 10.1111/ejn.15358
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal maternal separation affects metabotropic glutamate receptor 5 expression and anxiety‐related behavior of adult rats

Abstract: Exposure to early life stress leads to long-term neurochemical and behavioral alterations. Stress-induced psychiatric disorders, such as depression, have recently been linked to dysregulation of glutamate signaling, mainly via its postsynaptic receptors. The role of metabotropic glutamate receptor 5 (mGluR5) in stress-induced psychopathology has been the target of several studies in humans. In rodents, blockade of mGluR5 produces antidepressantlike actions, whereas mice lacking mGluR5 exhibit altered anxiety-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…Some studies using MS as a model for ELA have shown increased anxiety-like behavior in MS mice, particularly in males (Daniels et al, 2004 ; Malcon et al, 2020 ; Tsotsokou et al, 2021 ), although this is inconsistent (Fabricius et al, 2008 ; Bondar et al, 2018 ; Wang D. et al, 2020 ). On the other hand, numerous studies applying the LBN model have found that exposure to ELA does not affect anxiety-like behavior in the open field or elevated-plus maze test in male rats and mice (Naninck et al, 2015 ; Molet et al, 2016a ; Bolton et al, 2018a ; Bolton et al, 2020 , Figure 1B ).…”
Section: Sex-specific Behavioral Outcomes In Animal Models Of Early-l...mentioning
confidence: 99%
“…Some studies using MS as a model for ELA have shown increased anxiety-like behavior in MS mice, particularly in males (Daniels et al, 2004 ; Malcon et al, 2020 ; Tsotsokou et al, 2021 ), although this is inconsistent (Fabricius et al, 2008 ; Bondar et al, 2018 ; Wang D. et al, 2020 ). On the other hand, numerous studies applying the LBN model have found that exposure to ELA does not affect anxiety-like behavior in the open field or elevated-plus maze test in male rats and mice (Naninck et al, 2015 ; Molet et al, 2016a ; Bolton et al, 2018a ; Bolton et al, 2020 , Figure 1B ).…”
Section: Sex-specific Behavioral Outcomes In Animal Models Of Early-l...mentioning
confidence: 99%
“…Given these findings, the protracted consequences of eLA on adulthood emotional regulation are less intuitive. On one hand, increased anxiogenic behaviors and altered fear regulation are consistently detected in adult rodents with history of eLA, irrespectively from the kind of stressors (Brenhouse and Bath, 2019;Guadagno et al, 2020;Manzano Nieves et al, 2020;Tsotsokou et al, 2021). On the other hand, surprising findings are observed in the cortico-limbic pathway.…”
Section: Early-life Experience Shapes the Brain During Critical Perio...mentioning
confidence: 99%
“…Neonatal exposure to stressful environments is widely believed to be associated with impairments in brain development and adult behavior. Early life stress significantly increases the risk of visceral hypersensitivity and psychiatric disorders (1)(2)(3)(4). Both physical abuse and mental neglect in childhood are key environmental risk factors associated with the development of visceral pain and multiple psychiatric disorders, such as major depressive disorder and anxiety disorders (5).…”
Section: Introductionmentioning
confidence: 99%